Lexical Recognition in Deaf Children Learning American Sign Language: Activation of Semantic and Phonological Features of Signs. Issue 4 (3rd June 2020) - Lieberman, Amy M.; Borovsky, Arielle
Abstract: Children learning language efficiently process single words and activate semantic, phonological, and other features of words during recognition. We investigated lexical recognition in deaf children acquiring American Sign Language (ASL) to determine how perceiving language in the visual–spatial modality affects lexical recognition. Twenty native or early‐exposed signing deaf children (ages 4 to 8 years) participated in a visual world eye‐tracking study. Participants were presented with a single ASL sign, target picture, and three competitor pictures that varied in their phonological and semantic relationship to the target. Participants shifted gaze to the target picture shortly after sign offset. Participants showed robust evidence for activation of semantic but not phonological features of signs. However, in their behavioral responses, participants were most susceptible to phonological competitors. Results demonstrated that single word recognition in ASL is largely parallel to spoken language recognition among children who are developing a mature lexicon. Abstract :